RUSSIA IN CENTRAL ASIA: RETURN - KNIAZEV, Alexander (CENTRAL ASIA AND THE CAUCASUS, 2007)
In the 1990s Russia’s position in Central Asia became significantly eroded, not so much for economic reasons, as some Russian politicians allege, but because of its grossly misinterpreted national interests. It has become customary to associate the radical revision of Russia’s Central Asian policy with Vladimir Putin’s presidency. This is very true, but the events of 2000 were no more than the first steps toward fundamental changes. In 2005, the sovereign democracy conception marked a turning point in Russia’s foreign policy: the country finally placed its sovereignty above its foreign policy constants and began to slowly retreat from its previous devotion to the Western liberal-democratic principles. Sovereignty, understood as a synonym for the country’s political competitiveness, made great changes in Russia’s approach to the CIS: it sided with Uzbekistan in its post-Andijan conflict with the West and began pouring much more energy into the SCO and several other projects. The situation that had taken shape by 2004-2005 in the Western vector of Russia’s foreign policy and on its southern borders pushed the RF into Asian geopolitics. The U.S.-led military operation in Afghanistan allowed Russia to interfere more openly than before in the Central Asian political processes, which forced China to act accordingly. The Russian Federation could no longer ignore the new realities—the balance of power in the region of Russia’s vital interests was on the verge of being upset. In view of the changed style of Russia’s relations with the key international partners and the very real threats it encountered as soon as it began restoring its international status forced the Russian leaders to readjust the approach and very ideology of Russia’s foreign policy. It must stop being reflective: the country badly needs a well-substantiated and maximally long-term foreign policy strategy. This should be done not so much to restore the international balance or create a multi-polar world order: this is a new approach to the old problem of secure borders achieved either by their extension or by at least enlarging the “security zone” around Russia